2017
DOI: 10.1007/s10120-017-0699-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer treated by endoscopic submucosal dissection or endoscopic mucosal resection in Japan from 2004 through 2006: JGCA nationwide registry conducted in 2013

Abstract: Endoscopic resection of gastric cancer resulted in favorable short-term and long-term outcomes nationwide in Japan. Further efforts to increase the follow-up rate are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 24 publications
2
36
1
1
Order By: Relevance
“…The outcomes were similar to the results presented in the literature, with an en bloc R0 resection rate reaching 90% and a cure rate of > 80%, with a good safety profile [14, 15]. All adverse events (10.5% rate of bleeding and 0.9% rate of perforation) were controlled endoscopically and none of the patients needed surgery.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The outcomes were similar to the results presented in the literature, with an en bloc R0 resection rate reaching 90% and a cure rate of > 80%, with a good safety profile [14, 15]. All adverse events (10.5% rate of bleeding and 0.9% rate of perforation) were controlled endoscopically and none of the patients needed surgery.…”
Section: Discussionsupporting
confidence: 71%
“…This study confirmed the low risk of lymph node metastasis in expanded criteria patients and ESD as the best staging tool before surgery for EGC [3, 9, 15]. However, when lesions were divided into two groups of indications (absolute versus expanded indications), the second group presented lower rates of R0 (96.6 vs. 79.1%, p = 0.007) and curative resection (96.8 vs. 79.1%, p = 0.007), with an increased residual lesion rate (0 vs. 13.3%, p = 0.024), confirming a recent meta-analysis [24], although endoscopically treatable in most of the cases.…”
Section: Discussionmentioning
confidence: 52%
“…The indications of EGC for endoscopic resection may be reasonably expanded. However, the first and second expanded indications have recently been included as the updated absolute indications in Japan based on the evidence that EGC with prior expanded indications have a similar prognosis to those with prior absolute indications …”
Section: Endoscopic Resection Indications For Egcmentioning
confidence: 99%
“…Endoscopic resection, including endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD), has been regarded as standard treatment for early gastric cancers (EGC) . With the advances in endoscopic techniques, a 5‐year overall survival rate of more than 90% has been achieved in patients with EGC fulfilling the absolute or expanded endoscopic indications . Not only has the endoscopic treatment of EGC been widely applied in Asian countries but this technology has been gradually accepted and attracted the attention of endoscopists from Western countries …”
Section: Introductionmentioning
confidence: 99%
“…Die endoskopische Submukosa-Dissektion (ESD) ist eine insbesondere in Asien akzeptierte endoskopische Technik zur Behandlung von Magenfrühkarzinomen (MFK) [1,2]. Auch in Europa wird diese Methode immer häufiger angewendet [3,4].…”
Section: Introductionunclassified